An overview of sensitization dynamics in ferritic stainless steel welds - Amuda, Muhammed Olawale Hakeem; Mridha, Shahjahan (Hindawi Publishing Corporation, 2011)
Besides the problem of low ductility and poor notch toughness of ferritic stainless steel welds due to the microstructure characteristics of the weld section as a result of the weld heat input rate and the heat transfer factor, susceptibility to intergranular corrosion caused by the depletion of the chromium content of the weld matrix particularly in the HAZ is a major concern limiting the full deployment of the material in certain engineering applications regardless of its attractive economics combined with moderate strength and excellent corrosion resistance in alkali and acidic environments. Several attempts had beenmade to solve the problem. In the present work, a generic review of the sensitization problem in ferritic stainless steel welds as well as remediation techniques is presented. While stabilization is the most practiced prevention technique, it appears that the control of weld heat input and by extension the cooling rate is the ultimate option to prevent the onset of sensitization and control susceptibility to intergranular corrosion; however, the specific range of welding current and speeds that forms the given range of weld heat input needs to be determined.